Burden of thyroid cancer in North Africa and Middle East 1990–2019 - Seyed Aria Nejadghaderi (11651651) (2022)
Background Thyroid cancer is the leading cause of mortality and morbidity among cancers of the endocrine system. We aimed to describe the trends of thyroid cancer burden in North Africa and Middle East for 1990–2019. Methods Data on burden of thyroid cancer in North Africa and Middle East from 1990 to 2019 were obtained from the Global Burden of Disease (GBD) Study 2019. Decomposition analysis was used to estimate the effects of population growth, aging, and change in incident numbers on overall change of thyroid cancer incidence. Also, we used the comparative risk assessment framework of GBD to determine the burden of thyroid cancer attributable to a high body mass index (BMI). Results In 2019, the age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR) of thyroid cancer were 3.5 (2.9–4) and 0.5 (0.5–0.7) per 100,000, respectively. The highest age-standardized incidence, deaths, and disability-adjusted life year (DALY) rate were in Lebanon, Afghanistan, and United Arab Emirates, respectively. The ASIR of thyroid cancer in region was about 2.5 times higher among women, which had a positive association with increasing age. In 2019, the age-standardized deaths attributable to a high BMI was 16.7% of all deaths due to thyroid cancer. In 1990–2019, the overall change in thyroid cancer incident cases was a 396% increase which was mostly driven by the increase in disease-specific incidence rate (256.8%). Conclusions Women, the elderly above about 60 years old, and countries with a higher sociodemographic index showed higher incidence rates of thyroid cancer. Regarding our findings, it is recommended to establish preventive plans by modification in life style like weight reduction programs. Erratum: Burden of thyroid cancer in North Africa and Middle East 1990–2019: Frontiers in Oncology https://dx.doi.org/10.3389/fonc.2023.1208646, published online 28 April 2023. Other Information Published in: Frontiers in Oncology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fonc.2022.955358 Additional institutions affiliated with: WHO Collaborating Center for Healthy Ageing and Dementia - HMC